No Extravagance in Poems. A Linkage between Toegye's Poetic Aesthetics and Life Realm - Zheng-ying Ma; Heng-dong Xu (ESPES, 2022)
Experiences in the heart is one matter and literary writing is another: Toegye (1501-1570, a famous Korean Confucianist), however, would rather regard the two as a completely unified process, which amalgamates an immanent quality and a literary style, without isolation between them. Toegye stressed and valued the purity of the first experience, i.e., the filtered and the purified in the heart, which would flow into the second experience and purify it as well, ultimately cultivating it into a complete aesthetic experience. Poetry should be solely triggered by positive emotions, being aesthetically clear and pure, with no extravagance inside. A plain and ordinary style of literary writing is thereby formed and is regarded as a natural access of transcendence to a philosophical, ethical, and aesthetic connotation which is pure, rich, and profound, 'shaping to Sagehood' in Confucianism. Emotion plays the role of a cementing force that unifies all these factors and sections for life aestheticization.